Analisis Pengaruh Clearance terhadap Hasil Potong pada Proses Stamping Produk Member Floor Side Inner LH - Desy Agustin; Ibnu Syihab; Abdul Wahid Arohman; Edwin Sahrial Solih; Fredy Sumasto (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The development of production demands in the automotive industry has resulted in an increase in the need for various shapes and types of metal materials. Components used in automotive industrial production require the strength and durability of metal materials. The products produced in this sector are very diverse, including engine components, vehicle body parts and various vehicle accessories. To be able to meet customer demands for quality and efficiency, adequate production process support tools are needed, of course, such as dies. This tool is very suitable for making products from sheet metal with the same shape and in large quantities in a relatively short time. However, in making printing equipment (Dies) it does not require operation, it requires precise calculations so that accurate process results will be obtained, especially in calculations and clearance accuracy. Efforts to improve quality and efficiency in the product manufacturing process, for this reason, an analysis and improvement of the clearance of the cut results on SPC440 material with a thickness of 1 mm for the Member Floor Side Inner Lh product was carried out. The results of the improvement in the clearance of the part were able to optimize the clearance value from 0.06mm to 0.075mm